Intellectual Failure and Ideological Success in Organization Studies: The Case of Transformational Leadership. (April 2016) - Alvesson, Mats; Kärreman, Dan
This article discusses the current self-confidence and apparent success—at least by market/popularity measures—of leadership studies (LS) in general and transformational leadership (TFL) in particular. An alternative interpretation is offered, suggesting that it is the ideological character of these approaches that account for their "success, " at least in quantitative terms. Their wide appeal needs to be understood against the background of the fragmentation in the field before the entrance of these much more popularly appealing, but theoretically questionable ideas which lack credible empirical support. The article concludes that the currently popular streams are strongly structured by ideology—drawing on hero and religious mythologies—and suggests some ways to reduce the ideological overtone and the resulting tendency to produce tautologies and biased results.